A Longitudinal Study of Neurocognition in Dementia with Lewy Bodies Compared to Alzheimer’s Disease - Breitve, Monica H.; Chwiszczuk, Luiza J.; Brønnick, Kolbjørn; Hynninen, Minna J.; Auestad, Bjørn H.; Aarsland, Dag; Rongve, Arvid (Frontiers in Neurology, 2018)
Introduction: There are relatively few longitudinal studies on the differences in cognitive decline between Alzheimer`s disease (AD) and dementia with Lewy bodies (DLB), and the majority of existing studies have suboptimal designs. Aims: We investigated the differences in cognitive decline in AD compared to DLB over four years, and cognitive domain predictors of progression. Methods: In a longitudinal study, 266 patients with first time diagnosis of mild dementia were included and followed annually. The patients were tested annually with neuropsychological tests and screening instruments (MMSE, CDR, CVLT-II, TMT A & B, Stroop test, COWAT animal naming, BNT, VOSP Cubes and Silhouettes). Longitudinal analyses were performed with linear mixed effects (LME) models and Cox regression. Both specific neuropsychological tests and cognitive domains were analysed. Results: The current study sample comprised 119 AD and 67 DLB patients. In TMT A, the DLB patients had a faster decline over four years than patients with AD (p=.013). No other longitudinal differences in specific neuropsychological tests were found. Higher executive domain scores at baseline were associated with a longer time to reach severe dementia (CDR = 3) or death for the total sample (p=.032). High or low visuospatial function at baseline was not found to be associated with cognitive decline (MMSE) or progression of dementia severity (CDR) over time. Conclusions: Over four years, patients with DLB had a faster decline in TMT A than patients with AD, but this should be interpreted cautiously. Beyond this, there was little support for faster decline in that DLB patients had a faster decline in neuropsychologically tests and cognitive domains than in AD patients.